Pengaruh Rotasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Depok - Puput Widyaningsih; Syahrial Adin; Yulia Mujiaty (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Human Resources are a key factor in determining the success of an organization. To improve employee performance, proper management is required, including job rotation and the enforcement of work discipline. This studi aims to determine the influence of job rotation and work discipline on employee performance at the investment and one-stop integrated service office of depok city. This research uses a quantitative approach using a saturated sampling technique. Data were collected through questionnaires distributed to 59 respondents who are employees at the agency. The data analysis techniques used include data quality testing, assumption tests, hypothesis testing, and the coefficient of determinasi. The result showed that job rotation has a positive and significant effect on employee performance. Likewise, work discipline also has a significant positive effect on performance. Simultaneously, both independent variables show a significant influence on employee performance. Based on these results, it can be concluded that proper implementation of job rotation and improved work discipline can make a real contribution to enhancing employee performance in the institution.